FAKTOR YANG MEMPENGARUHI DIABETES MELLITUS TIPE 2 PADA LANSIA (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2024)
Type 2 diabetes mellitus is a disease caused by an elderly person's body being unable to produce sufficient amounts of insulin or unable to use insulin effectively. Various factors influence diabetes mellitus in older people, including those that can be modified and those that cannot be modified. This study aims to identify factors that influence type 2 diabetes mellitus in older people. Research design with a cross-sectional approach. This research used a questionnaire and was analyzed using Fisher's statistical test. This research was conducted in September involving 93 elderly people. The results showed that a family history of diabetes mellitus was correlated with the incidence of diabetes mellitus (p = 0.000), hypertension (p = 0.023) and body mass index (BMI) (p = 0.008). Smoking is not correlated with the incidence of diabetes mellitus (p = 0.584), and physical activity is correlated with the incidence of diabetes mellitus (p = 0.028). It is recommended to provide special education to patients and families about the importance of treating diabetes mellitus, either in groups or individually at least 2-3 times a month.
Keywords: Faktor Diabetes Mellitus; Lansia